The Determinants of Corporate Cash Holdings: Case of Agriculture Companies in Indonesia (Journal of Academic Finance, 2021)
Objective: Cash holdings are one of the fundamental financial decisions for the company. This study aims to examine the determinants of cash holdings in agricultural companies on the Indonesia Capital Market.Methods: The population in this study was all agricultural companies on the Indonesia Capital Market from 2012 to 2019. The sample was obtained through a purposive sampling method. Data analysis in this study used multiple regressions.Results: This study found that profitability, liquidity, and operating cash flow positively affect the cash holdings of agricultural companies in Indonesia. This study also finds that leverage, firm growth, and firm size have no effect on cash holdings in agricultural companies on the Indonesia Capital Market.Originality/Relevance: This study emphasizes the importance of profitability, liquidity, and operating cash flow as factors that affect the company's cash holdings for agricultural companies in Indonesia.Theoretical/methodological contributions: The results of this study strengthen and complement the results of previous research on the factors that affect a company's cash holdings. Social/management contributions: The findings of this study are important as an effort to map the condition of cash holdings of agricultural companies in Indonesia. This study also advises managers of agricultural companies in Indonesia to increase the company's cash holdings to anticipate future business risks.
Keywords: Cash Holdings, Financial Risk, Liquidity, Agriculture Companies.